The prevalence of headache in a population of health care workers and the effects on productivity costs / Prevalenza ed effetti sulla produttività della cefalea in una popolazione di lavoratori della sanità - Cristofolini, A.; Dalla Serra, P.; Scherillo, et al., G. (La Medicina del Lavoro, 2008)
Background: Headache is reported as one of the most frequent causes of lost work time and reduced work efficiency. Aims: The aim of this study was to determine the impact of headache and its consequences as regards absence from work among health care workers and reduced work efficiency. Methods: The prevalence of headache and its effects on ability in daily activities and work productivity were studied and assessed on occasion of the periodic health examination of 3,620 health care workers of the Provincial Health Care Trust, Trento, by means of the MIDAS disability scale and parameters derived from criteria established by the International Headache Society. Results: In the previous three months 27.1% had suffered from at least one episode of headache. The prevalence of migraine was 9.9%, with a significantly higher percentage among women (12.9%). The total administrative costs estimated per working year were about Euro 136,836 for migraine and about Euro 44,614 for tension-type headache (TTH). The prevalence and features of migraine and TTH were studied. Conclusions: Data regarding the prevalence of migraine were similar to the results reported in other studies. The vast majority of the individuals reported no absenteeism over the previous three months. The study confirmed that we should continue to manage the presumed jobrelated trigger factors in the best possible manner, counselling should be made available to health care workers during the periodic health examinations or upon request, and if needed, the patient should be sent to a neurology specialist for a free examination and appropriate pharmacological treatment. Prevalenza ed effetti sulla produttività della cefalea in una popolazione di lavoratori della sanità La cefalea viene riferita da vari autori come una delle più frequenti cause di assenza dal lavoro e di ridotta produttività lavorativa. Lo scopo di questo studio era di determinare la ricaduta della cefalea sui lavoratori, in termini di disabilità e il conseguente tasso di assenteismo e presenteismo. Nel corso degli accertamenti sanitari periodici di 3.620 lavoratori sanitari della Azienda Provinciale per i Servizi Sanitari della Provincia Autonoma di Trento è stata valutata la prevalenza di cefalea e le sue conseguenze sulla qualità di vita e sulla produttività sul lavoro tramite la scala di disabilità MIDAS ed alcuni parametri derivati dai criteri della International Headache Society. Il 27,1% dei pazienti riferiva di aver sofferto, nei tre mesi precedenti, di almeno un episodio di cefalea. La prevalenza di emicrania è risultata pari al 9,9%, con una percentuale significativamente più alta tra le donne (12,9%). I costi totali per l’amministrazione stimati sull’anno lavorativo sono stati di circa Euro 136.836 per l’emicrania e di circa Euro 44.614 per la cefalea tensiva. La prevalenza di emicrania non era molto diversa da quella trovata in altri studi. La larga maggioranza dei soggetti non ha riferito giorni di assenteismo nei precedenti tre mesi. Le indicazioni dello studio sono di continuare a gestire al meglio i presunti fattori scatenanti correlati al lavoro, offrire un’attività di counselling ai lavoratori nel corso della sorveglianza sanitaria periodica o a richiesta e, al bisogno, indirizzare il paziente al neurologo per una visita specialistica gratuita ed un trattamento farmacologico adeguato.